LINC-PINT suppresses cisplatin resistance in gastric cancer by inhibiting autophagy activation via epigenetic silencing of ATG5 by EZH2 - Zhang, Cheng; Kang, Tong; Wang, Xinyi; Wang, Jizhao; Liu, Lin; Zhang, Jiawei; Liu, Xu; Li, Rong; Wang, Jiansheng; Zhang, Jia (Frontiers in Pharmacology, 2022)
Resistance to cisplatin (DDP) is a major obstacle in the clinical treatment of advanced gastric cancer (GC). Long noncoding RNA (lncRNA) play a significant regulatory role in the development and drug resistance of GC. In this study, we reported tha t the lncRNA LINC-PINT was downregulated in DDP-resistant GC cells. Functional studies showed that LINC-PINT inhibited proliferation and migration of DDP-resistant GC cells in vitro, and overexpression of LINC-PINT could enhance the sensitivity of DDP-resistant GC cells to DDP. Further investigation revealed that LINC-PINT recruited enhancer of zeste homolog 2 (EZH2) to the promotor of ATG5 to inhibit its transcription, leading to the suppression of autophagy and DDP resensitization. Collectively, our results revealed how the LINC-PINT/EZH2/ATG5 axis regulates autophagy and DDP resistance in GC. These data suggest that LINC-PINT may be a potential therapeutic target in GC.